(untitled) (European Journal of Pure and Applied Mathematics, 2017)
The aim of this paper is to initiate and discuss the properties and characterizations of soft semi-T_i and soft semi-D_i( for i = 0, 1, 2) spaces at soft point by analyzing the relationship among them. We also introduce and explore the properties of soft S-continuous functions.